Foreign Direct Investment and Natural Resource Curse in Sub-Saharan Africa - Iklima, Itangishaka (International Journal o Business and Society (IJBS), 2025)
Africa is the second largest continent in the world, a region which is vast and endowed with natural resources of different types. Sub-Saharan Africa is a region of different countries, ethnicity, races, believes, languages and groups of people accommodating and understanding each value and norms. An underdeveloped region despite the high quality and vast range of natural resources endowment deposited in the region. The increasing number of people living under poverty is alarming and without a proper channel to make the system work for a better livelihood, life in this region will be unconducive to the majority. In view of this, this study investigates the role of foreign direct investment (FDI) on natural resources curse in the sub-Saharan African region over the period of 2011-2020. Using the panel data static model to analyse the effect of FDI inflows and natural resources rents on GDP in the sub regions of Sub-Saharan Africa such as Eastern, Central, Western and Southern Africa and the dynamic model to analyse the whole Sub-Saharan region while controlling other socioeconomic variables. Results show that there is a presence of natural resource curse in Sub-Saharan Africa as a whole but the some of the sub regions such as Southern Africa are not affected by the natural resource curse.